Analiz uskorenij chokkeistov-professionalov urovnja KChL - Zankovets, V. E. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Purpose: to create an informative methodology for testing speed abilities of hockey players based on the characteristics of accelerations (duration, distance, speed) performed by professional hockey players in KHL championship games. The study involved 20 professional hockey players of the KHL team "Ak Bars" Kazan aged from 22 to 40 years old. Results: on average, more accelerations in one period and in the game are performed by defenders. Most often, both forwards and defenders accelerate 1.0-1.9 s - this occurs in 68-69% of cases, accelerations lasting 2.0-2.9 s are found in 22-23%, duration 3.0-5.9 s - in 9-10%, and accelerations over 6 s are not found at all. Defenders equally often (41% each) accelerate both 2.0-5.9 and 6.0-10.9 m. Forwards more often accelerate 6.0-10.9 m - in 44% of situations against 35% at a shorter distance of 2.0-5.9 m. At a distance of 11.0-15.9 m, forwards accelerate in 14% of cases, and defenders- in 12%. Distances over 16 m are accelerated by both forwards and defenders quite rarely - in 6-7% of cases. The most informative tests for assessing speed qualities are 5 and 10 m sprints. The use of standard 27.5 or 30 m sprint tests, which are so widely used in hockey, is justified in the absence of timing gates.